Prevalence of Maternal Anemia in A Tertiary Care Hospital in Western Nepal - Anita Lamichhane; Sharmila Gurung; Kiran Panthee; Deekshya Shrestha (Journal of Nepal Medical Association, 2019)
Introduction: Maternal anemia is a common problem in developing countries like Nepal accounting for around 30-50% of women becoming anemic during pregnancy. The present study aims to find out the prevalence of maternal anemia in a tertiary care hospital in Western Nepal.